Reconstructing Islamic Educational Leadership: Negotiating Modern Managerial Rationality and Charismatic Authority in Indonesian Pesantren - Maskur; Indi Aunullah (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
The accelerating penetration of managerial rationality into Indonesian pesantren has generated a profound sociological tension between bureaucratic governance mechanisms and the enduring charismatic authority of the Kiai, producing competing sources of legitimacy that increasingly shape contemporary Islamic educational leadership. Situated within this context, the present inquiry seeks to transcend the binary opposition between managerial efficiency and spiritual authority through a reconstructed framework of leadership negotiation. Employing a qualitative philosophical-conceptual approach, the study utilizes critical content analysis and text-based hermeneutics to examine a corpus of literature spanning Western organizational sociology, theories of authority and managerialism, alongside scholarly works on pesantren, Islamic governance, and educational leadership. The analysis reveals that the uncritical adoption of bureaucratic instruments such as standard operating procedures, performance indicators, and formal accountability systems frequently generates operational paradoxes in institutional succession, financial governance, decision-making processes, and personnel loyalty. These tensions foster a zero-sum polarization in which administrative professionalism and charismatic legitimacy are often treated as mutually exclusive domains. The study formulates a Prophetic-Managerial Leadership model that repositions managerial efficiency as an operational engine functioning beneath the Kiai’s overarching spiritual and moral canopy. This framework offers a theoretically grounded pathway for reconfiguring governance structures, strengthening institutional sustainability, and guiding future policy development within contemporary pesantren and other Islamic educational institutions